Re-examining the Middle-Income Trap Hypothesis: What to Reject and What to Revive? - Xuehui Han; Shang-Jin Wei (Asian Development Bank (ADB), 2015)
Why do some economies grow faster than others? Do economies in the middle-income range face especially difficult challenges producing consistent growth? Using a transition matrix analysis on decade-level growth rates, we find that the data clearly reject the idea that middle-income economies either have a high absolute probability of being stuck where they are or have a higher relative probability of being stuck than the low- or high-income groups. In this sense, the notion of a "middleincome trap" is not supported by the data. However, economies in a given income range have different fundamentals and policies, and relative growth across economies may depend on these variables. Since development economists and practitioners have proposed a long list of variables that could affect growth, we employ a recently developed nonparametric classification technique (conditional inference tree and random forest) to decipher the relevance and relative importance of various growth determinants. We find that the list of variables that can help distinguish fast- and slow-growing economies is relatively short, and varies by income groups. For low-income economies, favorable demographics, macroeconomic stability, good education system, and good transport infrastructure appear to be the most important separating variables. For middle-income economies, favorable demographics, macroeconomic stability, sound global economic environment, and openness to foreign direct investment (FDI) appear to be the key discriminatory variables. This framework also yields conditions under which economies in the low- and middle-income range are trapped or even move backward.
hdl:11540/5052
Keywords: C14; C30; F01; F60; O11; O43; 330; conditional inference regression tree; economic growth; growth determinants; infrastructure; middle-income trap